TORTIKOLIS MUSKULAR KONGENITAL - Kawatu, Imelda E.; Angliadi, Engeline (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Torticollis, or wryneck, is a group of symptoms based on many causes that clinically manifests itself as a crooked or rotated neck. Congenital muscular torticollis is the most common type of congenital torticolllis which occurs in four per 1000 births and one per 300 live births with 75% of these cases on the right side. It was found that 90.1% of plagiocephalic cases incured this torticollis. In this condition, due to contractions of the neck muscles, the head turns and tilts to one side, meanwhile the chin points to the opposite side. Congenital muscular torticollis is caused by a shortening of the sternocleidomastoid muscle due to trauma during labour or abnormal fetal position in utero. Signs and symtoms of congenital muscular torticollis are recognized as early as two months after birth in which the head turns to one side associated with neck muscle hypertrophy, muscle spasm, and a limited range of motion (ROM). The management of congenital muscular torticollis consists of pharmacological, non-pharmacological, and surgical treatments. The prognosis is stated as good if there is a good improvement after 6 months of rehabilitation, but it is stated bad if there is no improvement after 6 months of treatment with a continuation of the asymetrical face. Keywords: congenital muscular torticollis, management   Abstrak: Tortikolis adalah kekakuan leher yang menimbulkan spasme otot yang secara klinis bermanifestasi sebagai leher yang bengkok atau terputar. Tortikolis bukan merupakan suatu diagnosis melainkan kumpulan gejala dengan berbagai gangguan yang mendasarinya. Tortikolis muskular kongenital ialah bentuk yang paling umum dari tortikolis kongenital dengan insiden sekitar 4 per 1000 kelahiran, dan 1 dari setiap 300 kelahiran hidup. Pada tortikolis muskular kongenital terjadi kontraksi otot-otot leher (75% terbanyak pada sisi kanan) yang menyebabkan posisi kepala turn dan tilt ke satu sisi dan dagu mengarah ke sisi yang berlawanan. Penyebab terjadinya tortikolis muskular kongenital ialah pemendekan otot sternokleidomastoid akibat trauma selama proses persalinan, atau posisi bayi dalam kandungan. Umumnya, gejala dan tanda klinis diketahui pada 2 bulan pertama dimana kepala mengarah ke arah sisi sakit, pembesaran otot-otot leher, spasme otot, dan keterbatasan lingkup gerak sendi leher. Penanganan tortikolis muskular kongenital terdiri dari farmakologis, non-farmakologis, dan pembedahan. Prognosis disebut baik bila tercapai hasil yang baik setelah 6 bulan terapi dengan penanganan rehabilitasi, dan memburuk bila tidak terdapat perubahan dalam 6 bulan terapi ditandai oleh wajah yang asimetris. Kata kunci: tortikolis muskular kongenital, penanganan